Soil organic carbon as affected by land use in young and old reclaimed regions of a coastal estuary wetland, China. (16th January 2013) - Bai, J.; Xiao, R.; Zhang, K.; Gao, H.; Cui, B.; Liu, X.
Abstract Soil organic carbon (SOC) and selected soil properties were measured in fringe and ditch marshes and cropland of old and young reclaimed areas in a subtropical estuary in China in order to investigate the effects of land use and reclamation history on SOC. The results show that after the conversion of wetlands to cropland, a longer reclamation history (>20 yr) resulted in greater soil bulk density, salinity, clay and silt, and lower soil moisture, SOC and sand content, whereas a shorter reclamation history (<20 yr) induced smaller values for soil pH, moisture and sand. Ditch marshes had greater average SOC in the top 50 cm than fringe marshes and cropland. SOC decreased generally down soil profiles from 0 to 50 cm in depth, except for the obvious accumulation of SOC in deeper soils from old fringe and young ditch marshes. Ditch marshes had the greatest SOC densities in the top 50 cm in both regions compared to the other land uses. SOC densities in the top 50 cm were less in croplands than in fringe marshes in the young region, while there were no significant differences between them in the older one. Except for cropland, SOC densities in the top 50 cm of the fringe or ditch marshes in the old region were not significantly different from those in the young region. SOC in both regions was reduced by 13.53 × 104 t (12.98%) in the top 50 cm of the marshes after conversion to cropland, whereas the regional SOC storage increased by 29.25 t when ditch marshes were included. The results from regression analysis show that bulk density and soil moisture significantly influenced SOC. The total SOC stored in both ditch marshes and croplands was higher compared to fringe marshes. The regional SOC storage in the top 50 cm was not reduced after reclamation due to C accumulation in the ditch marshes. The regional effects of cultural practices should be taken into account in devising strategies for managing soils in coastal wetlands, particularly in the developing world.